Clinical Trial Quality Assessment in Adult Spinal Surgery: What Do Publication Status, Funding Source, and Result Reporting Tell Us?. Issue 8 (October 2022) - Danford, Nicholas C.; Boddapati, Venkat; Simhon, Matthew E.; Lee, Nathan J.; Mathew, Justin; Lombardi, Joseph M.; Sardar, Zeeshan M.; Lenke, Lawrence G.; Lehman, Ronald A.
Study Design: Narrative Review Objectives: The objective of this study was to compare publication status of clinical trials in adult spine surgery registered onClinicalTrials.gov by funding source as well as to identify other trends in clinical trials in adult spine surgery. Methods: All prospective, comparative, therapeutic (intervention-based) trials of adult spinal disease that were registered onClinicalTrials.gov with a start date of January 1, 2000 and completion date before December 17, 2018 were included. Primary outcome was publication status of published or unpublished. A bivariate analysis was used to compare publication status to funding source of industry vs non-industry. Results: Our search identified 107 clinical trials. The most common source of funding was industry (62 trials, 57.9% of total), followed by University funding (26 trials, 24.3%). The results of 76 trials (71.0%) were published, with industry-funded trials less likely to be published compared to non–industry-funded trials (62.9% compared to 82.2%, P = .03). Of the 31 unpublished studies, 13 did not report any results onClinicalTrials.gov, and of those with reported results, none was a positive trial. Conclusions: Clinician researchers in adult spine surgery should be aware that industry-funded trials are less likely to go on to publication compared to non–industry-funded trials, and that negative trials are frequently not published. Future opportunities include improvement in result reporting and in publishing negative studies.